032 Clinical audit research and evaluation for motor neurone disease (CARE-MND): alignment with clinical care standards. Issue 12 (14th November 2019) - Beswick, Emily; Newton, Judith; Pal, Suvankar; Colville, Shuna; Davenport, Richard; Morrison, Ian; Swingler, Robert; Gorrie, George; Bateman, Antony; Chandran, Siddharthan
Abstract : Aims: To establish 14 Key Performance Indicators (KPIs) of clinical care to provide a prospective audit framework to review routinely collected data fields on the Care Audit Research Evaluation (CARE-MND). Based upon Scottish and UK motor neuron disease (MND) standards of clinical care outlined in HIS/QIS Neurological Standards (2009) and NICE MND Guidelines (2016). Methods: 14 KPI categories of clinical care were reviewed. The completion percentage of 53 fields from CARE-MND were analysed for deceased people with MND (pwMND) diagnosed between 01/01/2015 and 31/12/2018. Results: There was a 73% average completion in data capture for deceased patients diagnosed in the specified range for the 14 KPI areas of clinical care. Conclusions: The introduction of CARE-MND as a research register and tool to support clinical care has resulted in more complete routine data capture of information which can be used to audit and improve delivery of care. The KPI audit framework will be repeated in the future to assess variation in data capture.